Expansion of functionality and increase use information pyrovidicons termovision systems - Bozhenko, Valentina; Kondratov, Oleg; Kondratov, Petro (Видавництво Львівської політехніки, 2010)
Two-channel principle of infrared camera design that allows not only, on difference of existing devices,, to obtain stereo image of an object, but also to organize the procedure of frame-by-frame processing of both channel pyrosignals is proposed. The result of such processing consists in vital decrease of pyrovidicon targets geometric and pedestal noise influence, and useful signal increase and. consists in synchronous and asynchronous interferences.
Keywords: Termovision systems; infrared cameras; pirovidicon; pirosygnal